Detection of bovine herpesvirus 5 (BoHV-5) in formalin-fixed, paraffin-embedded bovine brain by nested PCR in colombian cattle - Pedraza, Francisco J [UNESP]; Alessi, Antonio C [UNESP]; Barbosa-Stancioli, Edel F (My University, 2010)
Fifteen cases of viral meningoencephalitis in Colombian cattle were tested by nested PCR analysis for the detection of bovine herpesvirus 5 (BoHV-5). All fatal cases had shown severe neurological signs and had occurred following natural outbreaks of the disease. The neurological infection was histologically characterized by mild to moderate inflammatory changes in the brain and cerebellum, including meningitis, mononuclear perivascular cuffing, gliosis, haemorrhage, and the presence of Gitter cells (macrophages) accompanying large areas of malacia. No intranuclear inclusion bodies were seen in any of the cases. Results from BoHV-5 molecular extraction analyses showed there were five positive cases thus confirming the presence of the virus in Colombia. © 2011 Universidad de Antioquia.
Detección de herpesvirus bovino 5 (BoHV-5) en cerebro incluido en parafina y fijado en formalina, por PCR anidada, en bovinos colombianos
Keywords: Bovine herpesvirus; Polioencephalomalacia; Viral encephalitis